Do tourist percept Croatia as a safe tourist destination? Presentation of the empirical evidence - Danijel Vucenovic; Angela Milenkovska Klimoska; Dino Manestar (UTMS Journal of Economics, 2020)
As one of the most developed industries in the world, Tourism experienced, and is still experiencing safety issues on daily basis, which left a significant effect on the world economy. This in particular resulted safety becoming one of the main parts of an integral tourist product, considering that it influences significantly the tourist s decision-making process of a potential tourist when choosing a holiday destination, as well as his intention to revisit. Bearing in mind previously mentioned, the importance and role of safety as a part of competitive tourist product is being researched within this paper, respectively tourist s perception of safety of a tourist destination in a decision-making process when choosing Croatia as a holiday destination. The goal of this paper is to provide a theoretical insight into the newest findings in the field of safety in tourism, to present the empirical results of a research conducted in Croatia, and based on these results to propose further improvement activities in order to improve the level of safety for tourists, and achieve further competitive positioning of Croatia as a safe tourist destination on the world tourist market.
Keywords: L83; Z30; 330; Safety in tourism; Croatia; safe destination